'This heart-rending and world-shattering news': gender, emotion, and transnationalism in the Bill Shankly retirement letters. Issue 1 (2nd January 2022) - McDougall, Alan
ABSTRACT: In July 1974, Bill Shankly, the charismatic manager of Liverpool FC, surprised the football world by announcing his retirement. During fifteen years in charge, Shankly revolutionised LFC, transforming a second-tier outfit into one of Europe's best teams. His impact on the city of Liverpool was equally profound. At times in the 1960s, Shankly's popularity eclipsed even that of the Beatles. His retirement, wrote one supporter, felt like 'the end of the world'. It triggered a public outpouring of grief, well wishes, and reminiscences. Based on previously unpublished material from the Shankly Family Archive, this essay examines the history, or histories, of the correspondence sent to Bill Shankly in the summer of 1974. Using three approaches – gender history, the history of emotions, and transnational history – it highlights under-explored aspects of football's rootedness in everyday life: female fandom, male sentimentality, and the first stirrings of Liverpool's international popularity. In Bill Shankly's football republic, collective identity was rooted in civic pride, but crossed age, class, gender, and national lines.